Relationship between financial management, religious commitment and employees’ knowledge of EPF investment / Noor Ellina Zulkifli, Ahmad Farid Ridhwan Zakaria and Kasmaruddin Che Hussin - Zulkifli, Noor Ellina; Zakaria, Ahmad Farid Ridhwan; Che Hussin, Kasmaruddin (2013)
In Malaysia, awareness in investment is still an indistinct issue among society. There are a lot of investment products being introduced by financial institutions and yet the initiatives to save for their life are step sided by many. In general, employees with savings from their contributions in EPF are more secure in terms of their financial standing. However, many studies have shown that there is considerable dissatisfaction with the returns it has provided to contributors through the management of its assets which is difficult to sustain their life for the remaining years out of the workforce. An increasing responsibility placed on individual employees in managing their investment and saving which demands them to have adequate knowledge about invesment. Therefore, this paper, subjectively, aimed at discussion on EPF investment among private sector’s employees in Dungun, Terengganu. Thus, a theoretical framework is developed to illustrate the relationship between financial risk tolerance, financial and investment knowledge, and religious commitment. This study utilised questionnaire-based surveys to solicit responses from employees who are working in private sectors in Dungun, Terengganu. Data collected from 200 employees were analysed using statistical procedures of SPSS version 19.0. Based on the investigation, the result reveals that there is significant relationship between all independent variables towards dependent variables. As a whole, the whole model is demonstrated that all the independents variables are able to explain 18.4% of the total variation dependent variables. The rest of 81.6% can be explained by undefined variables in this research.